The Effect of Burnout towards OCB in the Companies on Workers of PT.X and PT.Y - Wahyudi Rendiana Njoto; Stanley Miracle Boenawan (iBuss Management, 2015)
Companies are growing and competing with each other to be the leading business in its own sector. The companies will utilize its resources and use it effectively and efficiently in order to be on top. One of the resources is the companies’ human resource which is the workers that run the company altogether by doing their job description based on their position. The human resources could produce better results if their state of mind is in the prime condition. The research aims to know the effect of burnout towards Organizational Citizenship Behavior of the workers in PT. X and PT. Y. This would let the researchers and companies to identify the effect of burnout to OCB which would let the companies formulate strategies to maintain the workers to reach high productivity yet retaining the welfare and loyalty of the workers. The research was done by gathering data from 100 samples using random sampling. Then the data was analyzed using multiple regression. The result of the research showed that burnout gives significant effect towards Organizational Citizenship Behavior. Furthermore the relationship that the independent and dependent variables shows are positive relationship which is contrary to the research conducted before by previous researchers.Keywords: Human Resource, Workers, Burnout, Organizational Citizenship Behavior